A top-down approach to preparation of H-Y zeolite nanoparticles - S, Saepurahman Si; Hashaikeh, Raed; Kurniawan, Teguh (Asia-Pacific Journal of Science and Technology, 2021)
Zeolite is an aluminosilicate material formed of 3D pores containing channels and cages of many different topologies, including sodalite (SOD) and faujasite (FAU) framework types. H-Y zeolites (FAU-type framework) are widely used as active components of catalysts for petroleum refining and petrochemical processes. The archetypal H-Y zeolites used in the industry have a large particle-size morphology and there has recently been a growing interest in using zeolite nanoparticles (NPs) due to their desirable characteristics. Ball milling (BM) offers an easy, fast, and environmentally friendly way to produce zeolite NPs from commercially available zeolite microparticles. Although BM effectively reduces the particle size of zeolite, it is often accompanied by a reduction in crystallinity. In this report, a study was conducted with the intention of improving the crystallinity of H-Y zeolite NPs after BM. Alkaline leaching using NaOH was found to further reduce the particle size of the NPs, leading to an amorphous phase. In contrast, recrystallization in a dilute aluminosilicate solution transformed the H-Y zeolite from a FAU-type framework to the SOD type.